Come home already! (Harper, an imprint of HarperCollins Publishers, [Library Ideas, LLC], 2018)
An Amazon Best Book of the Month for Kids * A Bank Street College of Education Best Children's Books of the Year From the creators of Goodnight Already! and I Love You Already!, the third hysterical picture book about Duck and Bear, unlikely pals. <u5:p></u5:p> An excited Duck wants to hang out with Bear. But Bear's gone fishing for a whole week and is happy to finally get a second alone. <u5:p></u5:p> What will Duck do while Bear is gone? How will he survive without his best pal?!

Bob and Tom (Atheneum Books For Young Readers, 2017)
From the critically acclaimed author of The Perfect Pumpkin Pie and Snail and Slug comes a sweet picture book about two very bored turkeys who are trying to figure out what to do with their day. Throughout the day, starting at 7:45 a.m., two bumbling turkeys are very bored. What should they do today? Well, as they decide, they go through a whole day filled with adventure! Will that be enough to satisfy these two turkeys?

The Berenstain Bears and the ducklings (Berenstain Bears (I can read), , 1, 2018)
Join the Berenstain Bears as they prepare a warm welcome for the newborn ducklings in this sweet springtime addition to the classic New York Times bestselling series. After the Berenstain Bears help Farmer Ben with his chores, a pair of ducks mistakenly follow them home. But what comes next is a huge surprise for everyone—Brother and Sister find a nest filled with eggs! Berenstain Bears and the Ducklings is a Level One I Can Read book, which means it’s perfect for children learning to sound out words and read full sentences.

The secret valentine (Duck and Hippo, ,, 2018)
Join Duck, Hippo, and their friends as they uncover their secret valentines! It's Valentine's Day, and something curious is going on. As the birds tweet their love songs, Hippo and his friends Elephant, Pig, and Turtle each receive mysterious, unsigned Valentine's Day cards. Hippo wonders if his is from Duck; Elephant and Turtle think theirs are from Pig; and Pig dreams that hers is from Turtle. The cards tell the friends to come to the park at four o'clock to meet their valentines'so they'll find out soon enough! As the clock ticks away, the friends wonder'and dream'about their valentines and make special preparations. But when they arrive'sURPRISE! This Valentine's Day might not go exactly the way they expected, but one thing is certain: being friends with Duck and Hippo is always a special treat!

Duck, duck, dinosaur: snowy surprise (Duck, duck, dinosaur (Picture books), 1, 1, 2017)
Three eggs in a nest begin to wiggle and wobble, until CRACK! CRACK! CRACK! It’s a duck . . . duck . . . DINOSAUR!  Meet Feather, Flap, and Spike. They’re three unlikely siblings who each want to stand out. But together, they make the biggest splash! Perfect for families of all kinds, this playful, clever story has a dino-sized heart.

Bubble blast (Duck, duck, dinosaur (Picture books), 1, 1, 2017)
It's bath time for two little ducklings and one big dinosaur! Spike loves soap, but Feather and Flap don't want to scrub. What will Spike do to make getting clean fun for everyone? This short, sweet, and very bubbly story will help show kids how much fun bath time can be.

Duck! Rabbit! (Chronicle Books Llc, Chronicle Books LLC, Chronicle Books, Scholastic Inc, 2009)
This New York Times bestselling children's book is a smart, simple story that will make readers of all ages eager to take a side. From the award-winning team of author Amy Krouse Rosenthal and illustrator Tom Lichtenheld comes a clever take on the age-old optical illusion: is it a duck or a rabbit? Depends on how you look at it! Readers will find more than just Amy Krouse Rosenthal's signature humor here; there's also a subtle lesson for kids who don't know when to let go of an argument. ENGAGING AND THOUGHT-PROVOKING: Children will love the fun story based on the classic duck/rabbit visual puzzle, while parents will appreciate the book's lessons about differing points of view and right versus wrong. INCREDIBLE TALENT: Amy Krouse Rosenthal's award-winning children's books "radiate fun the way tulips radiate spring: they are elegant and spirit-lifting," according to the New York Times. Her 30+ books for kids include I Wish You More and Yes Day!, both illustrated by Tom Lichtenheld, and Dear Girl, Little Pea, Little Hoot, Little Oink, and Spoon. Tom Lichtenheld is a prolific creator and has illustrated many bestselling favorites, including Steam Train, Dream Train and several titles in the Goodnight, Goodnight, Construction Site series. RAVE REVIEWS: This bestselling book has earned multiple starred reviews. Highlights include: "The snappy dialogue makes for fine read-aloud. Duck? Rabbit? As kids will readily see, it depends on how you look at it."—Publishers Weekly, starred review "How cute is this? Really, really cute."—Booklist, starred review Perfect for: Parents, grandparents, and educators Fans of picture books like They All Saw a Cat, Hello Hello, Red is Best, and Where's the Duck?  Gift givers looking for a fun, interactive family read aloud book

The digger and the duckling (Digger series (Kuefler), , 1, 2022)
The perfect springtime gift for Easter, from the acclaimed author-illustrator of The Digger and the Flower. Ideal for fans of Sherri Duskey Rinker’s Construction Site series. Digger and the other big trucks love to build. But when a lost duckling waddles onto the jobsite, Digger and his friends learn to do more than just scoop and hoist and push . . . They learn to become a family. Share this beautiful picture book as a great introduction to taking care of the environment.

Duck & Goose (Duck and Goose (Picture books), 1, 1, 2007)
Honk and quack with these unlikely feathered friends as they explore the highs and lows of friendship! Now an animated series, available to stream on Apple TV+! Meet Duck and Goose, two young birds who mistake a polka-dot ball for an egg and have to master the art of cooperation—and sharing—to take care of it. But friendship is not always easy, as proved in this funny, accessible story. Young readers will instantly recognize themselves in these adorable and eternally optimistic characters. And this beautiful keepsake edition features extra content from the author on how to draw Duck & Goose. “Charming, funny, simple, and surprising. . . . Hills is master of the light comic touch.”—The Boston Globe

I'm a duck (Candlewick Press, 2018)
Sometimes it takes a lot to get your webbed feet wet! An adorable picture book makes a splash with a satisfying story about conquering your fears. I cannot swim, and that is bad. A landlocked duck is very sad. One day, an egg rolled out of a nest and right into a deep pond. Now that egg is a little duck, and the water is still very scary. Jumping into the pond at all seems impossible, never mind swimming in a line with all his brothers. “You’re a duck, and ducks don’t sink,” Big Frog points out. Practicing in a puddle helps a little, while backrubs and snacks from his mother help a little more. Big Frog offers to hold his friend’s wing and dive in together, but our little duck knows that some challenges need to be faced alone. Even when they are very scary!

The wild robot (Wild robot, 1, 1, 2018)
Soon to be a DreamWorks movie, coming to theaters 9/20/24! Wall-E meets Hatchet in this #1 New York Times bestselling illustrated middle grade novel from Caldecott Honor winner Peter Brown Can a robot survive in the wilderness? When robot Roz opens her eyes for the first time, she discovers that she is all alone on a remote, wild island. She has no idea how she got there or what her purpose is--but she knows she needs to survive. After battling a violent storm and escaping a vicious bear attack, she realizes that her only hope for survival is to adapt to her surroundings and learn from the island's unwelcoming animal inhabitants. As Roz slowly befriends the animals, the island starts to feel like home--until, one day, the robot's mysterious past comes back to haunt her. From bestselling and award-winning author and illustrator Peter Brown comes a heartwarming and action-packed novel about what happens when nature and technology collide.

The itsy bitsy duckling (Little Simon, 2017)
A fun and playful springtime twist on the popular nursery rhyme “The Itsy Bitsy Spider”! The itsy bitsy duckling swam in the waterway. Down came the rain and chased the snow away. Out came the sun as birds began to sing. The cold winter was over. At long last it was spring! The itsy bitsy duckling is ready for springtime as the other animals wake up from their long winter naps.

Quack! (Flowerpot Press, a division of Flowerpot Children's Press, Inc, 2018)
Ducks will be ducks in this silly story that encourages little ones to march to their own beat and be true to themselves. Readers will love to giggle and count along as our little duck friend encounters a growing number of silly animals in this hilarious read that also teaches counting from one to eleven.